The Image Detection of Pantograph Slide Based on Yang-shot Mode - 师鹏燕; 王黎; 高晓蓉; 杨凯; 周伟 (机车电传动)
At present, most of the pantograph slide images based on the image processing to detect slide wear are obtained by using overhead mode, but this way has some limitations for some complex arched. In this paper, a better way using yang-shot to capture pantograph slide images has been proposed. Firstly CCD cameras shoot the pantograph slide image, which transmit and store in the host detection by video capture card. Then process the save images , locate the edge of pantograph slide and contact wire, in order to provide the significant datas for pantograph slide wear test.